Antiviral activity of cathelicidin 5, a peptide from Alligator sinensis, against WSSV in caridean shrimp Exopalaemon modestus. Issue 93 (October 2019) - Xie, Qing; Liu, Yang; Luo, Fangmei; Yi, Qingqing; Wang, Yipeng; Deng, Lei; Dai, Jianfeng; Feng, Tingting
Abstract: White spot disease caused by white spot syndrome virus (WSSV) is responsible for harming shrimp aquaculture industry and results in a pandemic throughout the world. Cathelicidin 5 treatment enhanced immune parameters including antioxidant enzyme activity and immune-related genes expression in shrimp Exopalaemon modestus . Shrimp treated with cathelicidin 5 and inoculated with white spot syndrome virus (WSSV) exhibited a significantly lower mortality rate and lower viral VP28 amplification and expression than control. This study addresses the role of cathelicidin 5 in immune stimulatory and antiviral activities that could protect E. modestus from WSSV infection. Highlights: There is no Cytotoxicity of cathelicidin 5 in vitro and in vivo. Cathelicidin 5 could inhibit WSSV infection in vivo. Cathelicidin 5 could protect hepatopancreas during WSSV challenge. Cathelicidin 5 could increase caridean shrimp antioxidant enzyme activity. Cathelicidin 5 could up-regulate caridean shrimp immune-related genes expression.